Everything you need to know about step-families - Glassman, Bruce (New York : Rosen Pub. Group, 1988)
Discusses the problems and adjustments involved in having only one parent in the family and what happens when that parent remarries, giving the child a stepfamily.
Half title: Everything you need to know about stepfamilies.
Includes index.
Bibliography: p. 62.
Keywords: Stepfamilies -- United States -- Juvenile literature; Children of single parents -- United States -- Juvenile literature; Stepfamilies; Single-parent families; Remarriage